Sirtuin 7 Regulates Nitric Oxide Production and Apoptosis to Promote Mycobacterial Clearance in Macrophages - Zhang, Su; Liu, Yaya; Zhou, Xuefeng; Ou, Min; Xiao, Guohui; Li, Fang; Wang, Zhongyuan; Wang, Zhaoqin; Liu, Lei; Zhang, Guoliang (Frontiers in Immunology, 2021)
The host immune system plays a pivotal role in the containment of Mycobacterium tuberculosis (Mtb) infection, and host-directed therapy (HDT) is emerging as an effective strategy to treat tuberculosis (TB), especially drug-resistant TB. The current study revealed that expression of sirtuin 7 (SIRT7), a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase, was downregulated in macrophages after Mtb infection. Inhibition of SIRT7 with the pan-sirtuin family inhibitor nicotinamide (NAM), or by silencing SIRT7 expression, promoted intracellular growth of Mtb and restricted the generation of nitric oxide (NO). Addition of the exogenous NO donor SNAP abrogated the increased bacterial burden in NAM-treated or SIRT7-silenced macrophages. Furthermore, SIRT7-silenced macrophages displayed a lower frequency of early apoptotic cells after Mtb infection, and this could be reversed by providing exogenous NO. Overall, this study clarified a SIRT7-mediated protective mechanism against Mtb infection through regulation of NO production and apoptosis. SIRT7 therefore has potential to be exploited as a novel effective target for HDT of TB.